A self-assembling polycationic nanocarrier that exhibits exceptional gene transfection efficiency. Issue 111 (26th October 2015) - Sarkar, Kishor; Krishna Meka, Sai Rama; Madras, Giridhar; Chatterjee, Kaushik
Abstract : A novel polycationic gene carrier was prepared by conjugation of low molecular weight polyethyleneimine with gelatin through 4-bromonaphthaleic anhydride with exceptionally high transfection efficiency. Abstract : The lack of an efficient and safe carrier is a major impediment in the field of gene therapy. Although gelatin (GT), a naturally derived polymer, is widely used in drug delivery applications, it is unable to bind DNA efficiently. In this study, a novel polycationic gene carrier was prepared by conjugation of low molecular weight polyethyleneimine (LPEI) with GT through 4-bromonaphthaleic anhydride as a coupling agent to avoid self crosslinking. Self-assembly of LPEI conjugated GT (GT–LPEI) with plasmid DNA (pDNA) yielded nanoparticles with high gene complexation ability to form ∼250 nm cylindrical nanoparticles with a zeta potential of ∼27 mV. GT–LPEI showed exceptionally high transfection efficiency (>90%) in various mammalian cells including primary stem cells with minimal cytotoxicity. The transfection efficiency of GT–LPEI significantly surpassed that of many commercial reagents. The high gene transfection expression was confirmed in vivo . Thus, GT–LPEI is shown to be a promising nonviral carrier for potential use in gene therapy.